2006
DOI: 10.1002/elps.200600151
|View full text |Cite
|
Sign up to set email alerts
|

East Asian mtDNA haplogroup determination in Koreans: Haplogroup-level coding region SNP analysis and subhaplogroup-level control region sequence analysis

Abstract: The present study analyzed 21 coding region SNP markers and one deletion motif for the determination of East Asian mitochondrial DNA (mtDNA) haplogroups by designing three multiplex systems which apply single base extension methods. Using two multiplex systems, all 593 Korean mtDNAs were allocated into 15 haplogroups: M, D, D4, D5, G, M7, M8, M9, M10, M11, R, R9, B, A, and N9. As the D4 haplotypes occurred most frequently in Koreans, the third multiplex system was used to further define D4 subhaplogroups: D4a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 26 publications
(38 reference statements)
3
44
0
1
Order By: Relevance
“…Frequencies of mtDNA haplogroups are inferred from published data as follows: Hokkaido Jomon (Adachi et al, 2011); Okhotsk (Sato et al, 2009); Modern Ainu (Tajima et al, 2004);.Mainland Japanese (Maruyama et al, 2003); Ryukyu Islanders (Sekiguchi et al, 2008); Koreans (Lee et al, 2006); Han Chinese (Xu & Hu, 2015; Yao et al, 2002);.Nivkhi, Udegey, Negidal (Starikovskaya et al, 2005); Ulchi, Even (Sukernik et al, 2012); Koryak, Itel'men (Schurr et al, 1999). All populations except for the Edo Ainu, Okhotsk, and.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequencies of mtDNA haplogroups are inferred from published data as follows: Hokkaido Jomon (Adachi et al, 2011); Okhotsk (Sato et al, 2009); Modern Ainu (Tajima et al, 2004);.Mainland Japanese (Maruyama et al, 2003); Ryukyu Islanders (Sekiguchi et al, 2008); Koreans (Lee et al, 2006); Han Chinese (Xu & Hu, 2015; Yao et al, 2002);.Nivkhi, Udegey, Negidal (Starikovskaya et al, 2005); Ulchi, Even (Sukernik et al, 2012); Koryak, Itel'men (Schurr et al, 1999). All populations except for the Edo Ainu, Okhotsk, and.…”
Section: Resultsmentioning
confidence: 99%
“…Mainland Japanese (Maruyama et al, 2003); Ryukyu Islanders (Sekiguchi et al, 2008); Koreans (Lee et al, 2006); Han Chinese (Xu & Hu, 2015; Yao et al, 2002);.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The O2b subgroup is prominent in Korea, Japan, and Manchuria. (2) Fifteen mtDNA variations were annotated as the marker of ''D4'' haplogroup, which is prevalent in Korea (Umetsu et al 2005;Lee et al 2006). (3) A phylogenic tree drawn with 31,460 autosomal common SNPs within 93 individuals indicated that SJK has a common Korean autosomal makeup.…”
Section: Genetic Ancestry Of the Sjk Donormentioning
confidence: 99%
“…mtDNA were classified into haplogroups based on D-loop motifs of the specific sequences described in recent studies (Tanaka et al, 2004;Lee et al, 2006;Uchiyama et al, 2007). The mtDNA sequenced by M13 without setting the inner primers.…”
Section: Dna Analysismentioning
confidence: 99%